Writings and Representations of Education in Portuguese America - Thais Nívia de Lima e Fonseca (Universidade de Lisboa, 2016)
Beyond the analysis of educational processes present in the Luso-American society during the so-called Ancien Régime, it is necessary to focus on then current conceptions of education, and its appropriation by different walks of life in that society. On the Administrative, ecclesiastical, and legal fields, there was significant production of writing and, within it, representations of education characterized by its links with the most influential European intellectual production at the time, but also by the interposition of cultural environments in different parts of Portuguese America and the experiences of subjects in these regions. The objective of this work is the study of such representations of education by analyzing the writings present in the above pointed fields, in situations where the use of education-whatever its form-emerged as a solution to the problems present in the process of inserting America into the Portuguese Empire's context.